E-LKPD Bangun Datar pada Kolase Rumah Joglo Berbasis Etnomatematika Kelas IV Sekolah Dasar - Nurinawati Nurinawati; Insanul Qisti Barriyah; Moh Rusnoto Susanto (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The background of this research is the richness of Indonesian culture that is very diverse from Sabang to Merauke. Education and culture are now hot topics. Mathematics, as an important subject, is often considered difficult and boring due to monotonous learning and lack of motivation. Therefore, it needs improvement by connecting mathematical materials with local culture to make it more relevant in everyday life. The purpose of this research is to determine the effectiveness of E-LKPD flat shapes on the collage of Joglo traditional houses based on ethnomathematics in the mathematics learning process of flat shapes material which is expected to enable students to love their ancestral culture. The research method used is descriptive qualitative with the type of design research. Design research consists of 3 stages, namely experimental preparation, experimental implementation, and retrospective analysis. Data collection techniques with observation, questionnaires, and documentation. The results of the study are the implementation of E-LKPD collage based on ethnomathematics of Joglo traditional houses on flat shapes material runs effectively and can foster a sense of love for ancestral culture. This conclusion was obtained based on the suitability between ALT and HLT. Furthermore, the results of this study can be the basis for the development of the next E-LKPD by utilizing other cultures that are close to the daily lives of student.